2022
DOI: 10.2147/hiv.s361898
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of HIV Positive Serostatus Disclosure to Sexual Partner Among Individuals in Discordant Couples in Mbarara City, Southwestern Uganda

Abstract: Purpose Disclosure of HIV status is key in HIV management. Despite many studies on serostatus disclosure, there is a gap in experiences regarding HIV status disclosure among discordant couples. The current study addressed this research gap, and explored the lived experiences of serostatus disclosure among discordant couples in Mbarara City, South Western Uganda. Participants and Methods We conducted 12 in-depth interviews with the help of a translated interview guide, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Similarly, qualitative findings revealed that all participants who were staying with sexual partners had disclosed their serostatus to their sexual partners. Our findings are generally in tandem with the Malawian study by Shifraew et al; 30 the Ethiopian study by Shifraew et al, 30 , 39 a Nigerian study by Yaya et al, 40 and Ugandan studies by Atwijukire et al, 34 and Naigino et al, 32 where a big number of study participants who were staying with their partners had disclosed their HIV serostatus to their partners. The findings from the in-depth interviews indicate that several factors influenced HIV serostatus disclosure to sexual partners among study participants.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similarly, qualitative findings revealed that all participants who were staying with sexual partners had disclosed their serostatus to their sexual partners. Our findings are generally in tandem with the Malawian study by Shifraew et al; 30 the Ethiopian study by Shifraew et al, 30 , 39 a Nigerian study by Yaya et al, 40 and Ugandan studies by Atwijukire et al, 34 and Naigino et al, 32 where a big number of study participants who were staying with their partners had disclosed their HIV serostatus to their partners. The findings from the in-depth interviews indicate that several factors influenced HIV serostatus disclosure to sexual partners among study participants.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings are slightly consistent with the study done in Ethiopia where disclosure of HIV serostatus to a sexual partner was 92.6% (95%, CI = 90-95%), 30 and another one in Zimbabwe where 93% of the study participants disclosed their status, 31 and one in Uganda where 73.3% had disclosed 32 to sexual partners. However, most studies, unlike ours, disclosure was one-way 33 while other studies mainly focused on people living with HIV not necessarily on ART 30,34 except the study in Haiti where 75.2% of the study participants were on ART. 35 Some studies had smaller sample sizes like the Ugandan study by Ngonzi et al 36 which had 103 participants, the Malawian study by Hino et al 33 which had 40 participants and another Ugandan study by Atwijukiire et al, 34 with 12 participants compared to our study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Studies have recorded success stories resulting from the accurate application of the disclosure process, and most APHIV benefited from the disclosure process through empowerment and sustenance, as well as guidance on adherence to antiretroviral therapy (ART) [1,6]. However, there are unique issues in the current disclosure process that are not addressed by the guidelines and therefore undermine the main objective of disclosure [9,10]. The success of the disclosure process is determined by the reported positive coping skills by APHIV.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported major health problems after disclosure, such as high rates of mental health vulnerabilities (e.g., maladaptive coping mechanisms) and high-risk behaviors such as alcohol and substance abuse and risky sexual behavior [13][14][15]. Few studies have explored the experiences of APHIV on current disclosure practices both before and after disclosure [9,[16][17][18]. They are at the receiving end of the disclosure process, making their experiences vital to the effectiveness of the process.…”
Section: Introductionmentioning
confidence: 99%